Peço ajuda para resolver essa questão
Anexos:
![](https://pt-static.z-dn.net/files/d5d/ba058dbfefbecd86ea66cc21ed95c1c6.jpg)
Soluções para a tarefa
Respondido por
0
A) ![(x+y)^{2} = x^{2} +2xy+ y^{2} (x+y)^{2} = x^{2} +2xy+ y^{2}](https://tex.z-dn.net/?f=+%28x%2By%29%5E%7B2%7D+%3D+x%5E%7B2%7D+%2B2xy%2B+y%5E%7B2%7D+)
B)![(x-y)^{2} = x^{2} -2xy+ y^{2} (x-y)^{2} = x^{2} -2xy+ y^{2}](https://tex.z-dn.net/?f=+%28x-y%29%5E%7B2%7D+%3D+x%5E%7B2%7D+-2xy%2B+y%5E%7B2%7D+)
C)
B)
C)
Perguntas interessantes
Biologia,
1 ano atrás
Geografia,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás